Relationship Between Attachment and Social Skills in Adulthood Education in the Digital Society - Raquel Muñoz-Pradas; María de la Fuente Benítez; Antonio Palacios-Rodríguez; Mª Victoria Fernández Scagliusi (Societies)
In the midst of the Knowledge Society, where social interactions, contact, and the establishment of relationships—whether face to face or through the use of new technologies—prevail, isolation is detected as a consequence of the global COVID-19 pandemic, due to which both interpersonal relationships and attachment bonds are negatively affected. It is for all this that the need arises in this study to analyze the possible existence of a correlation between both variables. The objective of this work is to analyze the relationship between social skills and the type of attachment in a sample of subjects over 18 years of age. After carrying out the analyses, the existence of a statistically significant relationship was detected between the social skills variable and Attachment Scale 3, corresponding to subjects with good abilities to express feelings and comfort with relationships (secure attachment). It is concluded by stating that subjects who have developed a secure attachment will have more satisfactory social relationships.